Home
О нас
Products
Services
Регистрация
Войти
Поиск
igor20222
@igor20222
June 2023
1
3
Report
Подайте у вигляді многочлена стандартного вигляду вираз:
1)(5х2 + 8х – 7) – (2х2 – 2х – 12);
2)2х(х2+8х – 3);
3)(m – 4)(m + 5);
4)(4х – у)(2х – 3у).
Please enter comments
Please enter your name.
Please enter the correct email address.
Agree to
terms of service
You must agree before submitting.
Send
Answers & Comments
ilaffyvashie
1) (5x2 + 8x - 7) - (2x2 - 2x - 12) = (10 + 8x - 7) - (4 - 2x - 12) = 3 + 8x + 8 + 2x= 11 + 10x;
2) 2x x (x x 2 + 8x - 3)= 2 x x (2x + 8x - 3) = 2x x (10x - 3) = 20x(в квадрате) - 6x;
3)(m - 4) x (m + 5) = m x (m + 5) - 4 (m + 5) = m(в квадрате) + 5m - 4m - 20 = m(в квадрате) + 5m - 4m - 20 = m(в квадрате) + m - 20;
4) (4x - y) x (2x - 3y) = 4x x (2x - 3y) - y x (2x - 3y) = 8x(в квадрате) -12xy - 2xy + 3y(в квадрате) = 8x(в квадрате) - 14xy + 3y(в квадрате).
2 votes
Thanks 1
More Questions From This User
See All
igor20222
June 2023 | 0 Ответы
4 2 3 64989fc32f8c2
Answer
igor20222
June 2023 | 0 Ответы
ch3cooh 30
Answer
igor20222
June 2023 | 0 Ответы
80 6490f4d181e40
Answer
igor20222
May 2023 | 0 Ответы
077d5950939b600bbe5c52a71b708569
Answer
igor20222
May 2023 | 0 Ответы
60b27fa58a063f4b65c3a5798f1404d4
Answer
igor20222
March 2023 | 0 Ответы
a b m am ab 86 mb ab
Answer
×
Report "Подайте у вигляді многочлена стандартного вигляду вираз: 1)(5х2 + 8х – 7) – (2х2 – 2х – 12); 2)2х(х2+8х – 3); 3)(m"
Your name
Email
Reason
-Select Reason-
Pornographic
Defamatory
Illegal/Unlawful
Spam
Other Terms Of Service Violation
File a copyright complaint
Description
Helpful Links
О нас
Политика конфиденциальности
Правила и условия
Copyright
Контакты
Helpful Social
Get monthly updates
Submit
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
2) 2x x (x x 2 + 8x - 3)= 2 x x (2x + 8x - 3) = 2x x (10x - 3) = 20x(в квадрате) - 6x;
3)(m - 4) x (m + 5) = m x (m + 5) - 4 (m + 5) = m(в квадрате) + 5m - 4m - 20 = m(в квадрате) + 5m - 4m - 20 = m(в квадрате) + m - 20;
4) (4x - y) x (2x - 3y) = 4x x (2x - 3y) - y x (2x - 3y) = 8x(в квадрате) -12xy - 2xy + 3y(в квадрате) = 8x(в квадрате) - 14xy + 3y(в квадрате).